2015
DOI: 10.1007/s11270-015-2380-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Subcellular Distribution and Translocation and Grain Accumulation of Pb in Different Rice Cultivars

Abstract: To test the hypothesis that lead (Pb) content of rice grain may be related to its transport and subcellular distribution in rice plant, the present study was conducted with six rice cultivars of different types under different soil Pb levels. The results showed that grain Pb concentrations were correlated positively and significantly (P<0.05 or 0.01) with distribution ratios (DRs) of Pb from shoots to ears/grains, but insignificantly (P>0.05) with the DR from roots to shoots. The DR from shoots to ears/grains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This may be related to the mechanisms of Cd 2 þ translocation from roots to shoots via Ca channels (Mark 1990;Kim et al 2002) and endogenous Zn transporters by active transport (Pence et al 2000;Uraguchi & Fujiwara 2012). Pb precipitation in cell walls can decrease Pb transport from stem to grain (Liu et al 2015).…”
Section: Heavy Metal Transfer From Soils To Rice Plantsmentioning
confidence: 99%
“…This may be related to the mechanisms of Cd 2 þ translocation from roots to shoots via Ca channels (Mark 1990;Kim et al 2002) and endogenous Zn transporters by active transport (Pence et al 2000;Uraguchi & Fujiwara 2012). Pb precipitation in cell walls can decrease Pb transport from stem to grain (Liu et al 2015).…”
Section: Heavy Metal Transfer From Soils To Rice Plantsmentioning
confidence: 99%
“…In mature leaves, Sb concentrations >150 mg/kg are generally considered toxic [9]. Many recent studies have confirmed that different genotypes of the same species can differ in their accumulation and absorption of heavy metals (e.g., Chinese cabbage (Brassica chinensis L.) [30] and rice (Oryza sativa L.) [31]). To identify suitable C. bungei varieties for the remediation of Sb-contaminated soil, the ability of each genotype to absorb Sb should be considered.…”
Section: Discussionmentioning
confidence: 99%